Fuel efficient intelligent control of heavy trucks - Ahmed, H; Faris, Waleed Fekry; Akmeliawati, Rini (Asian Research Publishing Network (ARPN), 2016)
This work answers the need for improvement in fuel Economy in heavy duty vehicles (HDV’s), in a manner simple enough to be used in open road missions. A lookahead anticipatory control (LA) method is designed to adjust longitudinal motion (signified by velocity of the vehicle system) using knowledge of fluctuations in road grade. The prediction of driving behaviour is done using a fuzzy logic function based on a predefined rule-base. Control action of the brake and throttle positions are implemented by taking the state-dependent riccati Equation approach. The results of the proposed controller are compared against those of a standard PI cruise controller. Moreover, results of simulations on a 40 ton vehicle show the proposed method capable of increasing fuel economy.